The Axial Organ and the Pharynx Are Sites of Hematopoiesis in the Sea Urchin - Golconda, Preethi; Buckley, Katherine M.; Reynolds, Caroline R.; Romanello, Jennifer P.; Smith, L. Courtney (Frontiers in Immunology, 2019)
Background The location of coelomocyte proliferation in adult sea urchins is unknown and speculations since the early 1800s have been based on microanatomy and tracer uptake studies. In adult sea urchins (Strongylocentrotus purpuratus) with down-regulated immune systems, coelomocyte numbers increase in response to immune challenge, and whether some or all of these cells are newly proliferated is not known. The gene regulatory network that encodes transcription factors that regulate hematopoiesis in embryonic and larval sea urchins has not been investigated in adults. Hence, to identify the hematopoietic tissue in adult sea urchins, cell proliferation, expression of phagocyte specific genes, and expression of genes encoding transcription factors that function in the conserved regulatory network that controls hematopoiesis in embryonic and larval sea urchins were investigated for several tissues. Results Cell proliferation was induced in adult sea urchins either by immune challenge through injection of heat-killed Vibrio diazotrophicus or by cell depletion through aspiration of coelomic fluid. In response to either of these stimuli, newly proliferated coelomocytes constitute only about 10% of the cells in the coelomic fluid. In tissues, newly proliferated cells and cells that express SpTransformer proteins (formerly Sp185/333) that are markers for phagocytes are present in the axial organ, gonad, pharynx, esophagus, and gut with no differences among tissues. The expression level of genes encoding transcription factors that regulate hematopoiesis show that both the axial organ and the pharynx have elevated expression compared to coelomocytes, esophagus, gut, and gonad. Similarly, an RNAseq dataset shows similar results for the axial organ and pharynx, but also suggests that the axial organ may be a site for removal and recycling of cells in the coelomic cavity. Conclusions Results presented here are consistent with previous speculations that the axial organ may be a site of coelomocyte proliferation and that it may also be a center for cellular removal and recycling. A second site, the pharynx, may also have hematopoietic activity, a tissue that has been assumed to function only as part of the intestinal tract.